A halogen bonding assembled hybrid copper halide framework as a promising hypotoxicity photodetector. Issue 24 (3rd November 2022) - Liu, Guang-Ning; Li, Ming-Kun; Xu, Rang-Dong; Zhang, Ning-Ning; Quan, Xin-Jiao; Qian, Bing-Jing; Lu, Yi-Han; Li, Cuncheng
Abstract : The first halogen bonding assembled three-dimensional hybrid copper iodide was obtained by a facile and sustainable "All-in-One" synthesis strategy and shows great application potential as a hypotoxicity photodetector. Abstract : Copper has become a favored Pb-free candidate in the exploration of metal halide photoelectric materials; however, the known hybrid copper halides (HCHs) suffer from wide band gaps, low absorption coefficients or large exciton binding energies ( E b ), hindering their application as photodetectors. Combining functional aryl thioether with copper halide in one crystal lattice is greatly desired. However, it is impeded by the intricate and environment-unfriendly multi-step organic synthesis of aryl thioether, which involves harsh reaction conditions, toxic organic reagents and noble metal catalysts. Herein, we report the first Cl⋯Cl halogen bonding (XB) assembled HCH conductive framework with aryl thioether as ligand, {bis(5-chloropyridin-2-yl)sulfane(CuI)} n (BCS-CuI ). It was obtained by a well-designed facile and sustainable "All-in-One" synthesis strategy, where aryl halides, noble metals and harsh reaction conditions are not involved. Property measurements and theoretical calculations disclose that the XB assembled three-dimensional framework contributes significantly to the physical properties of BCS-CuI, which exhibits a small band gap of 2.44 eV, strong optical absorption and a relatively small E b value of 55.8 meV. Importantly, BCS-CuI exhibits great potential application as a hypotoxicity photodetector with a high photoresponse on/off ratio of 32.9 and carrier concentration and mobility superior to that of the well-known methylamine lead iodide (CH3 NH3 )PbI3 .